Clinical training in veterinary medicine: perspectives on quality and the role of specialists - Drzemalla, L.; Kleinsorgen, C.; Tipold, A. (Frontiers in Veterinary Science, 2025)
The practical year represents the transition between studies and professional work for students and is therefore a significant phase of clinical undergraduate training in Germany. Veterinary educational establishments are obliged to obtain information on elective practical training in order to assess the quality of clinical training. Since the constant increase in knowledge makes it necessary in many cases for veterinarians to specialize as part of postgraduate training, the influence of these specializations on clinical training of undergraduates should be investigated using a mixed-method design. An online survey was created for students and veterinarians as part of the quantitative data collection. Qualitative data collection was carried out in the form of guided interviews using a mixed-method design, with questions based on preliminary, selected results from the questionnaires. The majority of students surveyed were satisfied with the quality of training and supervision during their practical year (73%). The specialization of veterinarians was rated as “(very) important” by 52% for choosing a work placement for practical training. Around 40% of students felt that they received different levels of supervision from veterinarians with different qualifications. The veterinarians rated theoretical knowledge, communication skills and commitment of the students predominantly positively, but noted a deficit in practical skills. The specialization of veterinarians has an influence on theoretical education within the clinical training. The quality of training generally depends on the veterinarians’ level of knowledge and professional experience. The practical year gives students the opportunity to improve their practical skills before entering the profession, however for better outcomes and increased satisfaction, the objectives for elective practical training should be defined in advance between the practical training provider and the student.